Role of the Forkhead box family protein FOXF2 in the progression of solid tumor: systematic review - Yuzhen Zheng; Liusheng Wu; Zhenyu Hu; Hongying Liao; Xiaoqiang Li (Journal of Cancer Research and Clinical Oncology)
Abstract Background FOXF2 was reported to involve in a variety of biological behaviors that include the development of the central nervous system, tissue homeostasis, epithelia-mesenchymal interactions, regulation of embryonic development, and organogenesis. Purpose Understanding how FOXF2 influences the growth and development of cancer could provide valuable insights for researchers to develop novel therapeutic strategies. Results In this review, we investigate the underlying impact of FOXF2 on tumor cells, including the transformation of cellular phenotype, capacity for migration, invasion, and proliferation, colonization of circulating cells, and formation of metastatic nodules. In addition, we discuss the molecular mechanisms of FOXF2 in different cancers, including hepatocellular, esophageal, breast, colon, lung, prostate gland, as well as its role in embryonic development. Conclusion FOXF2 is a gene encoding a forkhead transcription factor belonging to the Forkhead Box family. The protein functions by recruiting activation transcription factors and basic components to activate the transcription of genes that interact with the complex. This review provides an in-depth analysis of the FOXF2’s function and pleiotropic roles in cancer development and progression.